New Implementations of Data Mining in a Plethora of Human Activities - Ochoa, Alberto; Ponce, Julio; Ornelas, Francisco; Jaramillo, Rubén; Zataraín, Ramón; Barrón, María; Gómez, Claudia; Martínez, José; Elias, Arturo (IntechOpen, 2011)
None